Conhecimento e prática de médicos e nutricionistas sobre a prevenção da alergia alimentar - Ribeiro, Camila Cury [UNIFESP] (2011)
Objective: To evaluate the knowledge and practice of pediatricians, gastroenterologists pediatricians, allergists and nutritionists regarding the primary prevention of food allergy. Methods: A descriptive cross-sectional study that enrolled pediatricians (n = 80), gastro-pediatricians (n = 120), allergists (n = 100) and nutritionists (n = 220), an amount of 520 professionals. The instrument collects used was a self-administered questionnaire prepared by the authors based on current recommendations of the major committees and societies related to prevention of food allergy. Results: The average age of professionals was 29.1 ± 5.8 years. The vast majority of the professionals was female, constituting a total 90.4% (n = 470) of respondents. The average time of graduation of professionals was 7.2 ± 5.8 years. Regarding the recommendation of exclusion diet on pregnancy, 89 (17.1%) professionals agreed with such practice, being the most indication by nutritionists. The gastro-pediatricians statistically differ from the others professionals by submitting the lowest rate of recommendation (p < 0.001). The recommendation of maternal exclusion diet on lactation was indicated by more number of professionals, constituting 40.8% (n = 212) of the sample, with the highest recommendation by nutritionists and pediatricians compared to pediatricians and allergists (p < 0.001). The duration of exclusive breastfeeding considered ideal was the period of 4 to 5.9 months indicated by 52.9% (n = 275) of professionals, according with the choices of most nutritionists, pediatricians and pediatricians. However, most allergists (65%; n = 65) indicated the range of 6 to 7.9 months. Regarding the time of introduction of complementary feeding, 218 (41.9%) professionals recommended modify the age of introduction to prevent the development of food allergy. The main period indicated was aged 6 to 7.9 months, indicated by 118 (54.1%) of respondents. Comparing the indication of the time of introduction of complementary feeding among professionals, 70 (70%) of allergists affirmed modify the time of introduction of complementary feeding (p < 0.001). The majority of special infant formulas indicated in case of impossibility of breastfeeding to prevent the development of food allergies were: Alfare® (70.6%), Neocate® (66.2%), Pregomin® (57.5%) and Nan HA® (42.1%). Conclusions: This study revealed there are misconceptions regarding the prevention of food allergy among all the categories of professionals. Our results confirm that the evaluation of knowledge and professional practice contributes to the definition of content that should be part of continuing education programs in the area of food allergy.